Management of Educational Curriculum Development from a Koranic Perspective in Improving the Morals of Students at Al-Washliyah 18 Tembung - Umi Kalsum; Nurdiani Nurdiani; Putri Syahri (Edumaspul: Jurnal Pendidikan, 2024)
The Islamic curriculum not only describes a series of knowledge that must be taught by educators (teachers) to students, but also all educational activities that are deemed necessary because they have an influence on students in order to achieve the goals of Islamic education. Among the educational activities that are considered urgent are instilling the values ​​of discipline and character education in children. This research: Management of the Islamic education curriculum is a necessity that must be carried out as an effort to increase the success of Islamic education. Because management essentially involves optimizing the work of school/madrasah institutions systematically and systemically to become the educational goals to be achieved which are colored with Islamic nuances. Based on this idea, it is necessary to carry out and implement educational curriculum management from a Koranic perspective in improving the morals of students at Al-Washliyah 18 Tembung.